2000
DOI: 10.1046/j.1460-9568.2000.00261.x
|View full text |Cite
|
Sign up to set email alerts
|

Late postnatal reorganization of GABAA receptor signalling in native GnRH neurons

Abstract: The molecular and cellular characteristics of the gonadotropin-releasing hormone (GnRH) neurons have been difficult to ascertain due to their scattered distribution within the basal forebrain. Using morphological criteria coupled with single cell RT-PCR postidentification, we have developed a method for investigating native GnRH neurons in the mouse brain and used it to examine the development of GABA(A) receptor signalling in this phenotype. Following the harvesting of the cytoplasmic contents of individual G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
121
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 130 publications
(127 citation statements)
references
References 43 publications
5
121
1
Order By: Relevance
“…The present results suggest a novel role for mGluRs: to inhibit GABAergic transmission directly to GnRH neurons. Because of the dominance of GABAergic contacts and synaptic transmission to these neurons (Sim et al, 2000;Jansen et al, 2003;, mGluRs may substantially impact GnRH neuron activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present results suggest a novel role for mGluRs: to inhibit GABAergic transmission directly to GnRH neurons. Because of the dominance of GABAergic contacts and synaptic transmission to these neurons (Sim et al, 2000;Jansen et al, 2003;, mGluRs may substantially impact GnRH neuron activity.…”
Section: Discussionmentioning
confidence: 99%
“…Functional GABAergic synaptic transmission to GnRH neurons via ionotropic GABA A receptors varies as a function of reproductive state, and these changes may help drive reproductive cycles and transitions between fertile and infertile conditions (Sim et al, 2000;Moenter, 2004a,b, 2005). Although the consequence of GABA A receptor activation in GnRH neurons is controversial (Sim et al, 2000;DeFazio et al, 2002;Han et al, 2002Han et al, , 2004Moenter et al, 2004;Moenter, 2004a, 2005), mechanisms regulating this key synaptic input are poised to play a major role in the central regulation of fertility (Jarry et al, 1988;Kasuya et al, 1999;Bilger et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, changes in synaptic regulation at puberty (both excitatory, via glutamate and the peptide, kisspeptin, and inhibitory, via GABA) leads to activation of the hypothalamic pulse generator, which promotes enhanced, pulsatile GnRH release that, in turn, regulates the secretion of luteinizing hormone (LH) from the pituitary (for review, Freeman, 1994;Ojeda and Urbanski, 1994;Ojeda et al, 2006). In adult subjects, inhibitory GABAergic inputs onto GnRH neurons promotes diminished action potential bursting activity and subsequent pulsatile GnRH and LH release (Sim et al, 2000;Nunemaker et al, 2003;Han et al, 2004;for review, Herbison et al, 1991;Moenter et al, 2003). A very interesting facet with respect to GABAergic control of GnRH neuron activity is that the developmental change in the chloride reversal potential (E Cl ), which causes GABA to switch from imparting depolarizing to hyperpolarizing effects, is dramatically delayed in GnRH neurons.…”
Section: Forebrain and Hypothalamic Regions Regulating The Expressionmentioning
confidence: 99%
“…For example, in rodents, it is quite clear that the population of GnRH neurons expressing c-fos at the time of the GnRH/luteinizing hormone (LH) surge resides predominantly, if not exclusively (Wintermantel et al, 2006), within the POA (Hoffman et al, 1993). Furthermore, studies in our own lab have found numerous instances where the morphology of (Cottrell et al, 2006), expression of receptors for neuromodulators (Jasoni et al, 2005;Grattan et al, 2007) on, or neurotransmitter effects (Sim et al, 2000;Pape et al, 2001;Clarkson and Herbison, 2006) on, adult GnRH neurons appears to be dependent upon their rostrocaudal location in the mouse; in particular whether they are located in the MS or POA. The underlying basis for this topographical heterogeneity remains unknown.…”
Section: Introductionmentioning
confidence: 99%